Response of Growth and Production of Upland Rice Plants (Oryza sativa L.) to Application of Vedagro Fertilizer and Green Manure - Noel Fernandus (Central Research Institute For Agriculture, 2023)
The aim of the study was to determine the response of growth and production of upland rice (Oryza sativa L.) to the application of vedagro fertilizer and green manure. Under the guidance of Mrs. Ir. Ernita, MP. This research was carried out in the experimental garden of the Faculty of Agriculture, Riau Islamic University, for four months from February to May 2021. The aim of the study was to determine the response of various doses of vedagro fertilizer and green manure to the growth of upland rice plants. The experimental design used in this study was a completely randomized factorial design consisting of two factors. The first factor was the dose of Vedagro (V) fertilizer which consisted of 4 levels: 0, 30, 60, 90 grams per plot and the second factor was the dose of green fertilizer (H) which consisted of 4 levels: 0, 1, 2, 3 kg per plot. . Parameters observed were plant height, number of productive tillers, flowering age, harvesting age, weight of full grain, weight of empty grain, weight of wet grain in a clump, weight of dry grain in a clump and weight of 100 dry grains. The data were analyzed statistically and continued with the honest significant difference test (BNJ) at the 5% level. The results showed that the application of vedagro and green manure gave a real response to all observed parameters. The best treatment was at the dose of vedagro fertilizer 90 g/plot and green manure 3 kg/plot (V3H3). The main factor of vedagro fertilizer gave a real response to all observation parameters. The best treatment was found at the vedagro fertilizer dose of 90 g/plot (V3). The main factor of green manure gives a real response to all parameter observations. The best treatment was at a green manure dose of 3 kg/plot (H3).